Assessment of Epizootic Ulcerative Syndrome (EUS) in Estuarine Fishes Collected from Arasalar Estuary, Puducherry State, India - Saravanan, S.; Rajendiran, A.; Sivakami , R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Fishes form an important source of cheap protein for people of many countries. The majority of the global production comes from freshwater aquaculture (58%) followed by marine (36%) and brackish water (6%). With an average increase in aquaculture production of 11% during the last decade, aquaculture has become the fastest growing sector of the world food economy However, fish diseases is now posing a great threat to achieve maximum production and has become a limiting factor to the success of aquaculture. Among the various diseases, Epizootic Ulcerative Syndrome (EUS) is a disease affecting a wide range of wild and farmed freshwater and estuarine fish which has spread across south-east Asia and India. From the fish survey, Food Fishes were collected from the Arasalar estuary, Puducherry State, India. The fish caught were identified and average 200 species of each fish were examined for EUS (Epizootic ulcerative syndrome) infection for the four seasons of the year (Pre-summer, Summer, Post-summer and Rainy season). The results of the number of fishes with EUS that could be identified in the different seasons are reported. Of the 75 fishes, that were examined, 12 were affected with EUS. This shows that 16% of the fishes were subjected to infection. Among Lizaparsia, 11 species were infected representing 14.6% of infection and among Mystus, seven fishes were infected forming 9.3% of infection. With regard to Oreochromis mossambicus, only four species were infected forming 5.3% of infection. With regard to Glossogobius giuris, nine species were infected thus 12% of infection. Nevertheless, during this period, the range of infection ranged from nil to 16%. During the pre-summer season, the percentage of infection again ranged from nil but to 12%. The maximum infection was noticed in Liza parsia (9 fishes) representing 12% infection, Puntius filamentosus (8 fishes) recording 10.6% followed by Glossogobius and Mystus (8%) and Oreochromis mossambicus (1.33%) infection respectively. During the summer and the post-summer season, none of the fishes that were investigated recorded any signs of EUS. Thus, an overall comparison reveals that the highest percentage of EUS was recorded in the rainy season followed by the pre-summer season and least in summer and post-summer season.